Malang Mangrove Conservation Business Strategy Development in the Perspective of SWOT Analysis - Noerchoidah (Universitas Dinamika, 2021)
Focuses on the marketing offers of Malang mangrove conservation in order to increase visitor trust and happiness. Malang mangrove conservation is able to compete fiercely in the market, allowing guests to come to Malang mangrove conservation without feeling threatened by the competition. It is essential to create a service marketing strategy for Malang mangrove conservation that it capitalizes on current strengths while avoiding potential weaknesses and threats. All of the following alternatives are available: expanding market share, boosting cooperative cooperation, and establishing links with academia, government, and industry. It is also possible to discover a new business opportunity. In addition to increase service quality, a number of government measures may increase visitor loyalty. Creating marketing objectives with other tourism organizations and improving the overall quality of service are just a few of examples. Exploration of a business's weaknesses and opportunities increasing the effectiveness of social media promotion and marketing would expedite the deployment process.